Sustained Safety and Efficacy of Once‐Daily Hydromorphone Extended‐Release (OROS® hydromorphone ER) Compared with Twice‐Daily Oxycodone Controlled‐Release Over 52 Weeks in Patients with Moderate to Severe Chronic Noncancer Pain. Issue 1 (18th April 2012) - Richarz, Ute; Waechter, Sandra; Sabatowski, Rainer; Szczepanski, Leszek; Binsfeld, Heinrich
<x xml:space="preserve">Abstract</x> Abstract Once‐daily hydromorphone extended‐release (OROS® hydromorphone ER) and oxycodone controlled‐release (CR) are semisynthetic, ER opioid analgesics with established efficacy. An open‐label, randomized, 24‐week, parallel group, flexible‐dose study demonstrated noninferiority of OROS hydromorphone ER vs. twice‐daily oxycodone CR in patients with chronic noncancer pain. In total, 112 patients were enrolled in a 28‐week, open‐label extension study; 60 patients received OROS hydromorphone ER and 52 received oxycodone CR. The primary efficacy measure was the change from baseline to Weeks 38 and 52 in Brief Pain Inventory item "pain right now." Global assessments of efficacy, dosing convenience, and tolerability were secondary endpoints. Mean change in "pain right now" from baseline to Week 38 was −3.0 (OROS hydromorphone ER) vs. −2.8 (oxycodone CR), and from baseline to Week 52 was −2.9 vs. −2.8; these changes were similar to the changes in the core phase (−2.1 vs. −2.1). Similar improvements were demonstrated for secondary assessments, including pain, pain interference, and quality of life. At Week 52, global assessment of efficacy was rated as "very good" or "good" by the majority of patients (OROS hydromorphone ER, 91.7%; oxycodone CR, 86.5%). More patients in the OROS hydromorphone ER group (35.0% vs. 21.2%) assessed mode of drug intake as "very convenient." The majority of patients receiving OROS hydromorphone ER (88.3%) and oxycodone CR (88.5%) rated tolerability as "good" or "very good" at Week 52; few patients discontinued treatment because of an adverse event (1.6% vs. 0.4%, respectively). The effectiveness of OROS hydromorphone ER and oxycodone CR was maintained through 1 year.